When do Firms with New CEOs Engage in M&A? Understanding the Timing of New CEOs' First M&A Announcements - Betschinger, Marie-Ann; Moschieri, Caterina; Bertrand, Olivier; Aidli, Mahmoud (Wiley, 2025)
New CEO appointments can create strategic uncertainty for stakeholders, potentially undermining the CEO's position. While the stakeholder uncertainty perspective suggests CEOs may act boldly to clarify their strategic intentions during early tenure, the CEO life cycle perspective proposes that CEOs avoid such moves during early tenure, as they still need to learn. This study integrates these views to examine whether and when new CEOs under high strategic uncertainty make bold strategic choices during early tenure. Focusing on first acquisitions – especially large and cross-border deals – we argue that new CEOs have a higher hazard of announcing an acquisition under high strategic uncertainty, namely, outsider CEOs and those whose appointments were more negatively received. Leveraging the time CEOs spend in their role as a conceptual bridge between the two perspectives, we argue that the acquisition hazard under high strategic uncertainty increases over early tenure, as CEOs gather information and learn. Analysing 873 new US CEOs (2004–2020) with an extended Cox hazard model, we find a generally higher hazard of first acquisition announcements for outsider CEOs and those with more negative appointment reactions, especially for bolder deals. Evidence on time dependence is mixed, but more pronounced for outsider CEOs and large acquisitions.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 16 - Paz, justicia e instituciones sólidas; acquisition hazard; boldness; CEO turnover; M&As; new CEOs; strategic uncertainty; time dependence; upper echelons